Simultaneous storm time equatorward and poleward large‐scale TIDs on a global scale - Habarulema, John Bosco (2016)
We report on the first simultaneous observations of poleward and equatorward traveling ionospheric disturbances (TIDs) during the same geomagnetic storm period on a global scale. While poleward propagating TIDs originate from the geomagnetic equator region, equatorward propagating TIDs are launched from the auroral regions. On a global scale, we use total electron content observations from the Global Navigation Satellite Systems to show that these TIDs existed over South American, African, and Asian sectors. The American and African sectors exhibited predominantly strong poleward TIDs, while the Asian sector recorded mostly equatorward TIDs which crossed the geomagnetic equator to either hemisphere on 9 March 2012. However, both poleward and equatorward TIDs are simultaneously present in all three sectors. Using a combination of ground‐based magnetometer observations and available low‐latitude radar (JULIA) data, we have established and confirmed that poleward TIDs of geomagnetic equator origin are due to ionospheric electrodynamics, specifically changes in E × B vertical drift after the storm onset.